A high-resolution, long-term wave resource assessment of Japan with wave–current effects. (December 2020) - Webb, A.; Waseda, T.; Kiyomatsu, K.
Abstract: The largest source of uncertainty in estimating annual energy production from a wave energy converter is natural variability. Standards recommend the collection of long-term on-site records, but with a concurrent requirement of dense data coverage, it becomes intractable to assess resources even at the feasibility development stage. Here, we provide uncertainty estimates of wave energy resources along the coast of Japan at 1 km resolution based on 21-year long numerical simulation, assuring a mean absolute percentage error of 4%. The uncertainties of the annual, seasonal and monthly climatologies are provided, and the epistemic uncertainty due to the effects of ocean current and finite depth on wave power estimation are quantified. Additionally, a significant wave height threshold is applied to exclude severe storm periods when devices are not in operation. The estimated total available wave power in Japan is 115.1 GW, whereas with a 3 m significant wave height threshold, it reduces to about 70 GW. Wave modeling under strong influence of ocean current is yet another source of epistemic uncertainty and the local and remote effects of strong current field are discussed. Results from the wave resource assessment are accessible to the public via a user-friendly web-based Geographical Information System, which was developed to help foster the use of marine renewable energy. Highlights: A 21-year long, 1 km resolution wave hindcast simulation was conducted to assess wave power in Japan. Estimated total available wave power is 115.1 GW, and reduces to about 70 GW with a 3 m significant wave height threshold. Annual, seasonal, and monthly wave power density means and variabilities were estimated. Wave-current interactions are included in wave power estimates. Large annual and seasonal variability is found and several favorable sites for wave power generation are identified.